Influence of the season of the year and the type of flask in the somatic embryogenesis in papaya var. Maradol rojo - Laisyn Posada-Pérez; Alexis Rodríguez; Rafael Gómez-Kosky; Maritza Reyes; Marisol Tejeda (Biotecnología Vegetal, 2009)
Somatic embryogenesis in papaya has been subjected to many researches. However, the effect of ex vitro and in vitro environment on this process has been little studied. The objectives of this work were to determine the influence of the seasons for fruit harvest at the formation of papaya somatic embryos stage, from zygotic embryos of immature fruits and the effect of the kind of culture flask on the formation and germination of somatic embryos stages. Results demonstrated that the season for the collection of immature fruits did not influence on the formation of somatic embryos. Besides the use of glass culture flaks allowed to obtain 63.7% of embryos that developed zygotic embryos. The best results were achieved using this kind of culture flaks, with a 90.7% germination of somatic embryos. Key words: in vitro culture, papaya, type of culture flask, zygotic embryos